Assessment of healthcare solid waste management practices for environmental performance: a study of hospitals in Himachal Pradesh, India. Issue 3 (22nd December 2020) - Thakur, Vikas; Sharma, Somesh
Abstract : Purpose: The day-by-day escalating quantity of healthcare waste (HCW), has made waste handling and management a challenging issue for ensuring environmental quality. Developing nations like India face huge difficulties in handling healthcare solid wastes (HCSW) because of the extra population burden. Hence, the present study seeks to evaluate the role of various stakeholders, under the following four performance areas: "collection and segregation of HCSW, " "storage and transportation of HCSW, " "special measures for handling HCSW" and 'awareness among the various stakeholders of handling and managing the HCSW." Design/methodology/approach: The study targets the primary data from 323 stakeholders across 35 hospitals in Himachal Pradesh, India, to assess the environmental awareness level among various stakeholders. Data were analyzed using preliminary descriptive statistics, and further statistical testing was done using one-way ANOVA in SPSS version 20.0. Findings: Results highlight that most hospitals lack the following areas: segregation of HCSW, marking of zones and bags carrying infectious HCSWs, inadequate transportation facilities, bad handling and storage practices and recycling without chemical disinfection. Practical implications: The study's findings will help the hospitals' administration and State Pollution Control Board to design training programs for all the stakeholders involved in managing HCSW. The proper recycling of the HCSW will reduce the adverse environmental impact and ensure the environmental quality within the hospitals and surroundings. The preparation of appropriate policy for the collection, storage and transportation of HCSW from the hospitals to the treatment centers will ensure the cleaner delivery of healthcare services to society. Originality/value: The present study is the first of its kind, where the primary data were collected from the various stakeholders involved in the handling of HCSW at various healthcare establishments (HCEs) in Himachal Pradesh, India.